rewrite f(x) = 2x - 1 shifted up three units and the slope increased by a factor of 3

A. f(x) = 5x - 4

B. f(x) = 6x + 2

C. f(x) = 6x + 3

D. f(x) = 5x - 2

1 answer

The original function, f(x) = 2x - 1, can be rewritten as f(x) = 2(x) + (-1).

To shift it up three units, we add 3 to the function, giving us f(x) = 2(x) + (-1) + 3 = 2x + 2.

To increase the slope by a factor of 3, we multiply the coefficient of x by 3, resulting in f(x) = 3 * 2x + 2 = 6x + 2.

Therefore, the correct answer is B. f(x) = 6x + 2.